2020
DOI: 10.1007/s00595-020-01970-3
|View full text |Cite
|
Sign up to set email alerts
|

Determining the difference in the efficacy and safety of self-expandable metallic stents as a bridge to surgery for obstructive colon cancer among patients in the CROSS 0 group and those in the CROSS 1 or 2 group: a pooled analysis of data from two Japanese prospective multicenter trials

Abstract: Purpose This study compared the feasibility and safety of endoscopic placement of self-expandable metallic stents (SEMSs) as a bridge to surgery (BTS) between patients with obstructive colorectal cancer (CRC) classified as ColoRectal Obstruction Scoring System (CROSS) 0 and those with CROSS 1 or 2. Methods We conducted a post hoc analysis of two prospective, observational, single-arm multicenter clinical trials and performed a pooled analysis of the data. In total, 336 consecutive patients with malignant color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The utility of colonic stenting has mainly been evaluated on the basis of the surgical outcomes, including long‐term survival and postoperative complications, of Japanese patients who were bridged for curative surgery 2–6,9 . The present study suggests that colonic stenting for decompression for obstructive colorectal cancer is as valuable and effective in patients who undergo systemic chemotherapy and palliative therapy as it is in patients who are bridged for curative surgery, which are partly supported by the findings of previous studies 7,12 …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The utility of colonic stenting has mainly been evaluated on the basis of the surgical outcomes, including long‐term survival and postoperative complications, of Japanese patients who were bridged for curative surgery 2–6,9 . The present study suggests that colonic stenting for decompression for obstructive colorectal cancer is as valuable and effective in patients who undergo systemic chemotherapy and palliative therapy as it is in patients who are bridged for curative surgery, which are partly supported by the findings of previous studies 7,12 …”
Section: Discussionsupporting
confidence: 83%
“…2,3 Decompression by colonic stenting for stenosis in advanced colorectal cancer has been used during bridging before curative surgery and systemic chemotherapy. 3,[5][6][7][8][9][10][11] The technical-and patient-related risk factors for colonic stenting have been identified in several Japanese studies in the last 3 years. [12][13][14][15][16][17] Regarding surgical outcomes, the advantages and disadvantages of colonic stenting for bridging for surgery were compared with those for emergency surgery and the trans-anal decompression tube in Japanese studies and were found to be controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this scoring system ranging from CROSS 0-2, a lower ability to eat soft solids results in a lower CROSS score. A recently pooled, post-hoc analysis of two prospective observational multicenter studies evaluated stricture degree in CROSS 0 (worse clinical state) versus CROSS 1 or 2 patients treated with SEMS as BTS (Ohki et al, 2020). Both clinical effectiveness and safety of SEMS were similar between CROSS 0 and CROSS 1 or 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ER of a primary tumour is still performed frequently for left-sided OCRC in a curative setting [7], and the effectiveness of DS as a BTS is also reported [8]. Recently, SEMS is increasingly used as a BTS [9, 10]. Although the advantages of these methods have been reported, the optimal treatment strategy for left-sided OCRC patients remains controversial.…”
Section: Introductionmentioning
confidence: 99%